Epidemiology of child injuries in Uganda: challenges for health policy - Renee Yuen-Jan Hsia; Doruk Ozgediz; Sudha Jayaraman; Patrick Kyamanywa; Milton Mutto; Olive C. Kobusingye (AOSIS, 2011)
Globally, 90% of road crash deaths occur in the developing world. Children in Africa bear the major part of this burden, with the highest unintentional injury rates in the world. Our study aims to better understand injury patterns among children living in Kampala, Uganda and provide evidence that injuries are significant in child health. Trauma registry records of injured children seen at Mulago Hospital in Kampala were analysed. This data was collected when patients were seen initially and included patient condition, demographics, clinical variables, cause, severity, as measured by the Kampala trauma score, and location of injury. Outcomes were captured on discharge from the casualty department and at two weeks for admitted patients. From August 2004 to August 2005, 872 injury visits for children